2017
DOI: 10.1111/dme.13403
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of erectile dysfunction in diabetes: a systematic review and meta‐analysis of 145 studies

Abstract: Erectile dysfunction may be common among men with diabetes, but its prevalence is still debated. We aimed to assess the relative prevalence of erectile dysfunction in diabetes searching major databases from inception to November 2016 for studies reporting erectile dysfunction in men with Type 1 and Type 2 diabetes mellitus. We conducted a meta-analysis of the prevalence [and 95% confidence intervals (95% CIs)] of erectile dysfunction in diabetes compared with healthy controls, calculating the relative odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
226
6
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(253 citation statements)
references
References 31 publications
10
226
6
11
Order By: Relevance
“…Almost one‐quarter of men with Type 2 diabetes in the present study population had ED. This estimate was smaller than those reported in other studies . The explanation for this difference could lie in the definition of ED used in the present study; we based this on a single question whereas other studies used validated questionnaires to assess ED.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Almost one‐quarter of men with Type 2 diabetes in the present study population had ED. This estimate was smaller than those reported in other studies . The explanation for this difference could lie in the definition of ED used in the present study; we based this on a single question whereas other studies used validated questionnaires to assess ED.…”
Section: Discussioncontrasting
confidence: 67%
“…Our results are conservative and warn of a higher prevalence of comorbid Type 2 diabetes with ED in Peru. In addition to the different instrument used to define ED, our study population was younger than that in many other studies addressing the association between Type 2 diabetes and ED; however, some studies with even younger populations have also reported a high prevalence of ED . This further supports the relevance of the role of ED ascertainment in assessing risk of Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 53%
“…In particular, diabetes causes or exacerbates various disorders in the cardiovascular system. 7,8 Diabetes mellitus erectile dysfunction (DMED) is difficult to treat in part because its primary cause, diabetes itself is difficult to treat, and many affected men avoid seeking timely medical attention. [2][3][4] In addition, it is also well-known that diabetes causes penile erection dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Overcoming these barriers is not a simple task, but is potentially worthwhile as ED is not only a health condition in of itself but can also be a symptom of cardiac disease as well as having an association with diabetes and depression while men experiencing poorer general health are less likely to be sexually active and more likely to report sexual problems . New ways of breaking down the barriers surrounding discussions of this condition, such as online information, can help in increasing clinical diagnosis of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Erectile dysfunction (ED) is common among older men and increases with advancing age . In addition to the significant emotional and relationship difficulties that these problems cause, ED is a recognised indicator of cardiovascular disease, and is associated with hypertension, diabetes, and depression . Those with poorer general health are also more likely to report lower levels of sexual activity and higher levels of sexual problems …”
Section: Introductionmentioning
confidence: 99%